Evaluation of Secondary Prevention Knowledge in Patients with Coronary Artery Disease - Gabriel Bálint; Zuzana Slezáková (Medicina)
Background and Objectives: Most patients with cardiovascular disease have limited health literacy and knowledge. The promotion of knowledge among patients with coronary artery disease is an integral part of health maintenance and the minimisation of secondary cardiac events. The aim of this study was to map the percent proportion of answers and scores obtained from them in the studied domains. Materials and Methods: In this cross-sectional study, a Coronary Artery Disease Education Questionnaire (CADE-Q II) was used to verify knowledge gaps in the five studied domains. In total, 253 patients with coronary artery disease completed the CADE-Q II, which targeted five domains: health status, risk factors, exercise, nutrition and psychosocial risk. Data were collected between June 2021 and November 2024. Results: An analysis of the data found a total mean CADE-Q II score of 61.05 ± 11.42 SD out of 93 points. Our research showed that the total mean score of a group of patients corresponded to an acceptable level of knowledge. Patients in the cohort provided a total of 7843 responses for the five study domains. In total, 46.8% of patients scored all answers correctly in terms of risk factors, 49.0% in terms of nutrition, 53.1% in terms of health status, 64.4% in terms of psychosocial risk, and 65.0% in terms of exercise. Conclusions: The use of the CADE-Q II questionnaire, with its focus on the studied domains, verifies patient knowledge and provides a foundation for education, the provision of effective information and the promotion of secondary prevention knowledge.